Pengukuran Aktivitas Pemasaran pada Media Sosial Instagram - Arie Indra Gunawan; Fatya Amalia; Widi Senalasari; Vanessa Gaffar (Universitas Diponegoro, 2021)
This study aims to measure and validate the variable constructs of marketing activity in Instagram social media. The results of this study will be very meaningful for the study and implementation of measurement of marketing activity in Instagram social media because currently Instagram is a social media that has a large customer base and has activity business therein. This study uses a questionnaire as a means of collecting data that is sent online. The population in this study were social media users who had done online transactions on Instagram social media as many as 352 respondents’ data were collected which were then performed statistical calculations. Confirmatory Factor analysis (CFA) and Exploratory Factor Analysis (EFA) were conducted to measure marketing activities on Instagram social media. The results recommend that the variable marketing activity on Instagram social media can be measured through 6 dimensions consisting of 20 indicator items. These dimensions are visual communication, relationship interaction, delivery of information, recommendations, personalization, and modern elements. All these dimensions and indicators are in construct and consistency declared valid for measuring Instagram social media marketing activities.Penelitian ini bertujuan untuk mengukur dan memvalidasi konstruk variabel aktivitas pemasaran dalam media sosial instagram. Hasil penelitian ini akan sangat berarti untuk kajian dan implementasi pengukuran aktivitas pemasaran dalam media sosial instagram karena saat ini instagram merupakan media sosial yang memiliki basis pelanggan yang banyak dan terdapat aktivitas bisnis di dalamnya. Penelitian ini menggunakan kuesioner sebagai alat pengumpul data yang dikirimkan secara online. Populasi pada penelitian ini adalah pengguna media sosial yang pernah melakukan transaksi online di media sosial Instagram sebanyak 352 data responden berhasil terkumpul yang kemudian dilakukan penghitungan statistik. Confirmatory Factor Analysis (CFA) dan Exploratory Factor Analysis (EFA) dilakukan untuk mengukur aktivitas pemasaran dalam media sosial instagram. Hasil penelitian merekomendasikan bahwa variable aktivitas pemasaran pada media sosial instagram dapat diukur melalui 6 dimensi yang terdiri dari 20 item indikator. Dimensi tersebut adalah komunikasi visual, interaksi relasi, penyampaian informasi, rekomendasi, personalisasi, dan unsur modern. Kesemua dimensi dan indikator tersebut secara konstruk dan konsistensi dinyatakan valid untuk mengukur aktivitas pemasaran media sosial instagram.